Gonad Maturity Stages in Dentex maroccanus (Valenciennes, 1830) (Sparidae) and Length-Weight Relationships in the Syrian marine waters (Journal of Hama University, 2022)
The aim of this study is to determine the length-weight relationships (LWRs), morphological and histological development of the gonads in (345) specimens of Morocco dentex, Dentex maroccanus (Valenciennes, 1830) caught in the Syrian marine waters, during the period: 1/1/ 2019 to 31/12/ 2020, using various fishing tools, especially trammel.The following measurements were taken for each individual who were studied: the total length and weight to nearest 0.1 cm and 0.01 g, respectively. The relationship of the length calculated for male and female thumbnail, has reached values (b) calculated 3.2144 for males and 3.5379 for females, and 3.3162 for all studied individuals. Thus, it was observed that the calculated b value was greater than the ideal value, that is, the growth of the fishes of this type is Positive Allometric growth. The value of appreciation (R2 ) was close to all individuals, and was 0.8999 for females and 0.9459 for males and 0.9274 for all individuals.The results of the morphological study of the stages of development of the male and female gonads morphologically and histological in the studied fish species agreed with the hexagonal scale of gonad maturation, and individuals appeared in the stage of sexual inversion in various length groups.
Keywords: Dentex maroccanus, Sparidae, L-W Relationships, morphology and histology gonads changes, Syrian coast, Mediterranean sea.